MAXTUMQULI - SHEKSPIRI TURKMANNING - Quramboyeva, G. (SCIENCE and SOCIETY, 2024)
In this article discusses the influence of the great Turkmen poet Makhtumquli Firoghi’s poetry on Uzbek and Karakalpak literature.